Early Devonian trilobites from the Sierra de Las Minitas, northernmost Precordillera (La Rioja province), Argentina - Rustán, Juan José (2011)
Early Devonian trilobites are described based on material from Sierra de Las Minitas, in the northern extent of the Precordillera, western Argentina. This diverse fauna, the first one known from La Rioja Province, includes a species of the phacopid Paciphacops (Paciphacops) Maksimova, the calmoniids Talacastops zarelae Edgecombe, Vaccari and Waisfeld and Tormesiscus Waisfeld, Edgecombe and Vaccari, together with a proetid (Unguliproetus? sp.) and a dalmanitid. Fossils are preserved in nodules within a strongly folded dark and bioturbated shaley succession, included in a structural and stratigraphically complex geological setting. The taxonomic composition and taphonomic signature of the studied fossil locality are closely similar to those recognized within the lower part of the Talacasto Formation at Las Aguaditas section in San Juan Province. Lithologic and faunistic similarities allow a reliable stratigraphic correlation between both localities; therefore, the trilobite bearing rocks from the Sierra de Las Minitas are interpreted as the northernmost outcrops of the Talacasto Formation in the Argentine Precordillera and are considered to be Lochkovian in age. The remarkable lateral continuity of this fossiliferous stratigraphic interval indicates, as previously suggested, the development of a wide muddy-shelf setting in the Early Devonian Precordillera Basin.